The risk and severity of preeclampsia secondary to iodine deficiency and iodine deficiency-mediated subclinical hypothyroidism: mechanisms and early cardiovascular consequences - Businge, Bitamazire Charles (Department of Medicine, 2022)
Background Iodine deficiency affects about 2 billion people globally and is the leading cause of Subclinical (SCH) and overt (OH) hypothyroidism that are some of the risk factors of preeclampsia. Iodine deficiency in pregnancy, which can be corrected by supplementation, has been suggested in the past three decades as a risk factor for preeclampsia. It is uncertain if this is mainly because of elevated thyroid-stimulating hormone (TSH) in women with iodine deficiency complicated by hypothyroidism. Alternatively, it may be because of reduced serum antioxidant capacity and other pathways that are associated with the more prevalent inadequate iodine intake in pregnancy, or both. Aims The current thesis had three major objectives: 1) To determine the burden of iodine deficiency in pregnancy in Africa; 2) To find out if there is an association between iodine deficiency in pregnancy, subclinical hypothyroidism, endothelial dysfunction and preeclampsia; 3) To find out possible mechanisms through which iodine deficiency in pregnancy may predispose to preeclampsia, eclampsia, endothelial dysfunction and early cardiovascular pathological changes. Methods In the first part of this thesis, two systematic reviews are presented. The first was carried out in order to estimate the burden of iodine deficiency in pregnancy in Africa. This was complemented with a regression analysis using the more readily available school-age children (SAC) median urinary iodine concentration (UIC) and the limited pregnancy median UIC data to estimate the level of iodine nutrition in pregnancy in all the African countries. The second systematic review was carried out to find out the relationship between inadequate iodine intake in pregnancy and preeclampsia. In the second part of this thesis, we present results of case-control studies in which women with preeclampsia, severe preeclampsia, eclampsia and normotensive pregnant controls were enrolled at Nelson Mandela Academic Hospital (NMAH) and Mthatha Regional Hospital (MRH) in Eastern Cape South Africa. Their iodine nutrition status, thyroid function, endothelial dysfunction and arterial stiffness were compared by assaying the urinary iodine concentration (UIC), thyroglobulin (Tg), thyroid-stimulating hormone (TSH), triiodothyronine (T3), thyroxine (T4), nitric oxide (NO), oxidised low-density lipoprotein (oxLDL), pulse wave velocity (PWV) and aortic augmentation index (AI). In the third part of the thesis, two studies aimed at exploring mechanisms through which iodine and other micronutrient deficiencies together with environmental factors predispose to preeclampsia and eclampsia are presented. The first is a study using Factor Analysis to find out how various nutritional and inflammatory markers interact in different pathways to predispose to preeclampsia using data collected at Lomo Medical Centre, Kinshasa Province, Democratic Republic of Congo. The second is a case-control study in which we compared the thyroid function status, urinary iodine and serum potassium of women with eclampsia, severe preeclampsia and normotensive pregnant controls to find out if iodine deficiency, the resultant thyroid dysfunction and serum potassium levels were associated with the risk of eclampsia. Results Prevalence of iodine deficiency in pregnancy in Africa: results from systematic reviews and meta-analyses and pregnancy median UIC estimated from SAC median UIC Pregnancy iodine nutrition status data was available for 23/54 African countries. Between 2005 and 2020 a few African countries had sufficient (pregnancy median urinary iodine concentration [pMUIC] 150 - 250 μg/L), most had mildly inadequate (pMUIC 100 - 149 μg/L), and some moderate-to-severe inadequate iodine nutrition in pregnancy (pMUIC < 0.01, I2 >50). There was a non-significant risk of preeclampsia for women with UIC < 0.001) and the Pulse Wave Velocity 5.1, 5.7 and 6.3 m/s respectively for Eastern Cape normotensive, preeclampsia and severe preeclampsia women (p< 0.05). In linear regressions, TSH, age and hypertensive disease were independent predictors of elevated PWV which is associated with endothelial dysfunction and future cardiovascular disease. Possible mechanisms in the pathophysiology of preeclampsia associated with iodine deficiency, resultant thyroid dysfunction and other nutritional or inflammatory factors Using data of normotensive and preeclamptic women from Kinshasa Province, Democratic Republic of Congo, we have characterised four main pathophysiological pathways through which low iodine intake in pregnancy may predispose to preeclampsia. These are the interactions between selenium/iodine deficiency and elevated serum TSH, leading to endothelial dysfunction; serum ferritin, gamma-glutamyl transferase (GGT), C-reactive protein (CRP) and low urinary iodine excretion precipitating inflammatory oxidative stress. The others are elevated serum high sense-CRP (hs-CRP) and Rheumatoid factor subclinical inflammation and immune cell activation and high T3/T4 ratio acute TSH stimulation of thyroid with low thyroid iodine stores that may lead to excessive superoxide and hydroxyl production further exacerbating oxidative stress and endothelial dysfunction. Iodine deficiency, thyroid dysfunction in the pathophysiology of eclamptic fits Eclamptic women in the Eastern Cape (South Africa) had significantly lower urinary iodine concentration (UIC), free triiodothyronine (FT3), median serum potassium (K), but higher serum thyroglobulin (Tg) than women with severe preeclampsia and normotensive pregnant controls. The median values respectively for participants with eclampsia, severe preeclampsia and normotensive controls were UIC 69.5, 95.7, and 169.5 µg/L; FT3 3.8, 4.4 and 4.7 pmol/L; K 3.7, 4.2, 4.3 mmol/L; and Tg 39.0, 22.4, 19.5 µg/L. Low serum T3 and T4 levels coupled with a preferential transfer of T4 across the blood-brain barrier alter the physiological T3/T4 ratio in the CNS attenuating the inhibitory effects of GABA while the excitatory function of glutamate remains intact. Low serum potassium further attenuates GABAB receptor mediated tonic extra-synaptic inhibition resulting in net motor neurone stimulation and increased predisposition to the involuntary tonic-clonic convulsions observed in eclampsia. Conclusion There is still a high prevalence of inadequate iodine intake in pregnancy in Africa estimated to affect 45% of the African nations 25 years after commencement of iodine fortification of salt and other foodstuffs. While the complication of goitre and cretinism may have reduced, pregnant women in Africa may still be prone to high risk of preeclampsia, eclampsia, future cardiovascular disease and various degrees of reduced psychomotor development of the foetus depending on the severity and duration of insufficient iodine intake in pregnancy. Alternative measures need to be considered to mitigate the persistently high prevalence of iodine deficiency in pregnancy in Africa and other areas around the globe despite national salt iodization programs and other iodine fortification efforts that have been implemented for several decades. This will help reduce the risk of preeclampsia, eclampsia and related complications.